Selective recruitment of beneficial microbes in the rhizosphere of maize affected by microbial inoculants, farming practice, and seasonal variations - Ioannis D. Kampouris; Theresa Kuhl-Nagel; Jan Helge Behr; Loreen Sommermann; Doreen Babin; Davide Francioli; Rita Zrenner; Susanne Kublik; Michael Schloter; Uwe Ludewig; Kornelia Smalla; Günter Neumann; et al. (Environmental Microbiome)
Abstract Background Plant beneficial microorganisms as inoculants can improve crop performance, but factors affecting their impact on plant performance under field conditions remain unclear, thereby limiting their use in farming. Here, we investigated how farming practices (e.g., tillage and N-fertilization intensity) and growing seasons influenced the impact of a beneficial microorganism consortium (BMc: Trichoderma, Bacillus, and Pseudomonas strains) in maize and affected the rhizosphere competence of each BMc strain. In addition, we tested whether the consortium affects the resident rhizosphere microbiome and crop performance. In two growing seasons (2020 and 2021), we assessed how BMc inoculation affects maize growth, nutritional status, gene expression, and rhizosphere microbiome under different farming practices at the flowering stage. Results Inoculated strains successfully colonized the maize rhizosphere independently of farming practice. BMc inoculation improved plant growth and iron uptake in 2020, regardless of farming practice. These effects co-occurred with lower precipitation levels in 2020 compared to 2021. BMc inoculation reduced the expression of several stress-related genes in maize in 2020 under drought. An increased iron uptake by the BMc-inoculated plants was observed in 2020 and was associated with the upregulation of the gene ZmNAS3, which is linked to iron uptake. Therefore, BMc inoculation mitigated the drought impact on maize. The microbial rhizosphere communities were altered by BMc inoculation in both years, but patterns of responder taxa differed between seasons. Metagenome analysis revealed that more genes (e.g., genes encoding biosurfactants and siderophores) were enriched in the rhizosphere of BMc-inoculated plants in 2020 than in 2021. Moreover, we identified bacterial and fungal taxa positively associated with maize iron uptake. The relative abundance of these iron uptake-associated bacterial and fungal taxa significantly increased due to BMc inoculation in 2020, while they showed overall higher relative abundances in 2021, independently of BMc inoculation. We mapped the sequences of these iron-associated taxa to publicly available genomes and verified the occurrence of various plant beneficial traits in several mapped genomes. Conclusions Overall, we show that the growing season determined the effect of BMc inoculation on maize plants by shaping microbiome composition and function in the maize rhizosphere more than farming practice. These findings highlight the importance of the complex interplay between microbial inoculants and the resident rhizosphere microorganisms under abiotic stress conditions.